The Stranger Who Bore Me: Adoptee-Birth Mother Interactions - March, Karen R. (My University, 1990)
This study examines the long-term effects of adoption reunion. The main focus is on adoptees who have searched, made contact with their birth mothers and encountered a reunion experience. Intensive, open-ended interviews with a randomly-selected sample of sixty adoptees indicate that search and reunion have little connection to the adoptee's dissatisfaction with his/her adoption outcome or his/ her adoptive parent-child bonds. In fact, a large number hide their search and reunion from their adoptive parents because they do not want these significant others to think that they are unhappy with their adoptive status. The desire to reunite is more likely to be precipitated by some life-crisis event that raises the adoptive role-identity to a prominent position in the adoptee's salience hierarchy. Consideration of the meaning of that role-identity leads the adoptee to resolve the ambiguities that he/she encounters because of his/her lack of knowledge about his/her biological origins. Reunion contact resolves this sense of uncertainty because. it provides the missing background information that the adoptee needs for a consistent presentation of self in social interaction. Reunion contact with the birth mother is not a necessity for satisfactory reunion outcome. The adoptee possesses a strong vocabulary of motives that he/she uses to account for his/her reunion outcome and to integrate his/her background information as a part of his/her positive self-concept.
Keywords: Adoption; Mother interactions; Community Engagement; Family, Life Course, and Society; Place and Environment; Social Psychology and Interaction; Sociology; Community Engagement